The impact of leadership on student outcomes: how successful school leaders use transformational and instructional strategies to make a difference - Day, C; Gu, Q; Sammons, P (SAGE Publications, 2016)
Purpose: This article illustrates how successful leaders combine the too often dichotomized practices of transformational and instructional leadership in different ways across different phases of their schools’ development in order to progressively shape and “layer” the improvement culture in improving students’ outcomes. Research Methods: Empirical data were drawn from a 3-year mixed-methods national study (“Impact Study”) that investigated associations between the work of principals in effective and improving primary and secondary schools in England and student outcomes as defined (but not confined) by their national examination and assessment results over 3 years. The research began with a critical survey of the extant literature, followed by a national survey that explored principals’ and key staff’s perceptions of school improvement strategies and actions that they believed had helped foster better student attainment. This was complemented by multiperspective in-depth case studies of a subsample of 20 schools. Findings: The research provides new empirical evidence of how successful principals directly and indirectly achieve and sustain improvement over time through combining both transformational and instructional leadership strategies. The findings show that schools’ abilities to improve and sustain effectiveness over the long term are not primarily the result of the principals’ leadership style but of their understanding and diagnosis of the school’s needs and their application of clearly articulated, organizationally shared educational values through multiple combinations and accumulations of time and context-sensitive strategies that are “layered” and progressively embedded in the school’s work, culture, and achievements. Implications: Mixed-methods research designs are likely to provide finer grained, more nuanced evidence-based understandings of the leadership roles and behaviors of principals who achieve and sustain educational outcomes in schools than single lens quantitative analyses, meta-analyses, or purely qualitative approaches. The findings themselves provide support for more differentiated, context sensitive training and development for aspiring and serving principals.